Report of 2 Novel Presentations of Subcutaneous Fat Necrosis of the Newborn - Susanna M.H. Kannenberg; H. Francois Jordaan; Willem I. Visser; Fatima Ahmed; A. Fourie Bezuidenhout (MDPI AG, 2019)
Subcutaneous fat necrosis of the newborn (SCFNN) is a rare form of panniculitis classically affecting healthy full-term infants. There are a number of predisposing factors including perinatal asphyxia. The condition generally has a benign course with spontaneous resolution, but monitoring for metabolic complications, in particular the potentially life-threatening complication of hypercalcaemia, is critical. The authors report 2 cases of preterm infants with perinatal asphyxia with atypical presentations of SCFNN: the first with bony involvement resembling Langerhans cell histiocytosis and with follicular pseudocarcinomatous hyperplasia on histology; and the second presenting with a huge haematoma requiring surgical debridement. Both cases were initially erroneously diagnosed as pyogenic infections.